Predictors of Optimal Cognitive Aging in 80+ Women: The Women’s Health Initiative Memory Study - Goveas, Joseph S. (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND. Independent predictors of preserved cognitive functioning and factors associated with maintaining high preserved cognitive function in women ≥80 years remain elusive. METHODS. Two thousand two hundred twenty-eight women with a mean age of 85 years who participated in the Women’s Health Initiative Memory Study were classified as cognitively normal (n = 1,905, 85.5%), mild cognitive impairment (n = 88, 3.9%), dementia (n = 121, 5.4%) or other cognitive impairment (n = 114, n = 5.1%) by central adjudication. Global cognitive functioning was assessed using telephone interview for cognitive status-modified in those women who did not meet cognitive impairment criteria. Differences between women grouped by cognitive status with respect to each potential risk factor were assessed using chi-squared tests and t-tests. Backward stepwise logistic regression was used to select factors that were independently associated with cognitive status. RESULTS. Factors associated with preserved cognitive functioning were younger age, higher education, and family incomes, being non-Hispanic white, better emotional wellbeing, fewer depressive symptoms, more insomnia complaints, being free of diabetes, and not carrying the apolipoprotein E-epsilon 4 allele. Cognitively normal women who demonstrated sustained high preserved cognition were younger, more educated, and endorsed better self-reported general health, emotional wellbeing, and higher physical functioning. CONCLUSIONS. Addressing sociodemographic disparities such as income inequality, and targeting interventions to improve depressive symptoms and vascular risk factors, including diabetes, may play an important role in preserving cognition among women who survive to 80 years of age. Person-centered approaches that combine interventions to improve physical, cognitive, and psychosocial functioning may promote maintenance of high preserved cognitive health in the oldest-old.